2008
DOI: 10.1016/j.biomaterials.2007.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Affinity manipulation of surface-conjugated RGD peptide to modulate binding of liposomes to activated platelets

Abstract: Platelet adhesion, activation and fibrinogen-mediated aggregation are primary events in vascular thrombosis and occlusion. An injectable delivery system that can carry thrombolytics selectively to the sites of active platelet aggregation has immense potential in minimally invasive targeted therapy of vascular occlusion. To this end we are studying liposomes surface-modified by fibrinogen-mimetic RGD motifs that can selectively target and bind integrin GPIIb-IIIa on activated platelets. Here we report liposome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 31 publications
2
92
0
Order By: Relevance
“…Further studies demonstrated that cyclic arginine-glycine-aspartic-liposomes had even higher affinity for activated platelets than their linear counterparts [99,100]. In another study, Sialyl…”
Section: Other Approaches Include the Modification Of Liposomes With mentioning
confidence: 97%
“…Further studies demonstrated that cyclic arginine-glycine-aspartic-liposomes had even higher affinity for activated platelets than their linear counterparts [99,100]. In another study, Sialyl…”
Section: Other Approaches Include the Modification Of Liposomes With mentioning
confidence: 97%
“…The binding affinities of some of the RGD-containing derivatives for α v β 3 range from 3.2 to 100 nM. 85,86 The addition of specific amino acid residues to peptide sequence motifs, such as RGD, that induce binding to cell-attachment proteins, strongly enhances the binding affinity of this peptide. The injection of the modified peptides induced antigen-specific serum antibodies.…”
Section: Peptidesmentioning
confidence: 99%
“…24,25 The structure is identified by NME spectra, in Figure S1 and Figure S2. Figure 6 shows that, in vitro, 0.1 μM ingredient of AERL.…”
Section: Rosmarinic Acid Downregulates P-selectin Expressionmentioning
confidence: 99%